Manifiesto: Semillero de Investigación Contranarrativas - Orozco , Silvia; Vargas , Yovana; Vega Moreno, Gabriela; Hernández Contreras, Daniela; Flórez Aristizábal, Adriana; Botello , Slenka; Salgado, Sergio; Nur, Natalia; Rey, Laura; Blanco, María Fernanda (Back Projection, 2024)
Manifiesto de reflexión colectivo del Semillero de Investigación Contranarrativas